Correction to: Is there a critical rate of torque development? (European Journal of Applied Physiology, (2024), 10.1007/s00421-024-05647-4) - Abdalla, Leonardo Henrique Perinotto [UNESP]; Greco, Camila Coelho [UNESP]; Denadai, Benedito Sérgio [UNESP] (Springer Nature, 2025)
In the original version of this article, footnote of Table 3 was mistakenly included in the “Results” section under the “All-out test” section as 3rd paragraph and in the Table 3 footnote was missing. Table 3 footnote should have read. Data are presented as mean ± SD. Abbreviations: KE, knee extensors; PF, plantar flexors; ET, end-test torque; criti- cal RTD, critical torque development rate; MVC, maximal contraction voluntary. N = 9.